COVID-19 imported cases and severity: expected information from genomic characterization of SARS-CoV-2 strains in Mozambique - José Sumbana; Alfeu Passanduca; Salvatore Rubino (Journal of Infection in Developing Countries)
Introduction: The novel coronavirus, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), etiological agent of coronavirus disease 2019 (COVID-19) was first reported in China in December 2019 and spread worldwide. As of March 6th, 2021, there have been 116,670,105 million confirmed cases globally including 2,592,085 deaths. COVID-19 cases have been reported in 219 countries and territories, creating global panic. Mozambique has witnessed the evolution of COVID-19 epidemic associated with the weakness of health system, mostly in terms of laboratory diagnosis capacity, concerns on compliance to effective public health measures including physical distancing, use of masks in crowded indoor areas, hand hygiene, isolation and quarantine of people.